2004
DOI: 10.1002/ijc.20175
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone, a sesquiterpene in subtropical ginger, suppresses skin tumor initiation and promotion stages in ICR mice

Abstract: We recently showed that zerumbone, a sesquiterpene found in subtropical ginger, suppresses colonic tumor marker formation in rats and induces apoptosis in colon cancer cell lines. In our present study, the anti-tumor initiating and promoting activities of zerumbone in mouse skin were evaluated using a conventional 2-stage carcinogenesis model. A single topical pretreatment to mouse skin (2 mol) 24 hr before application of dimethylbenz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 66 publications
8
97
0
2
Order By: Relevance
“…Abundance of phytochemicals have been investigated and evidenced to be a promising chemopreventive agent. Eugenol, resveratrol, zerumbone and zapotin are among reported phytochemicals which warrants further investigation as chemopreventive agents attributable to their anti-tumor effects during initiation, promotion, or a combination of both stages (Murakami et al, 2004;Cuendet et al, 2008;Kalra et al, 2008;Pal et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Abundance of phytochemicals have been investigated and evidenced to be a promising chemopreventive agent. Eugenol, resveratrol, zerumbone and zapotin are among reported phytochemicals which warrants further investigation as chemopreventive agents attributable to their anti-tumor effects during initiation, promotion, or a combination of both stages (Murakami et al, 2004;Cuendet et al, 2008;Kalra et al, 2008;Pal et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers also observed that zerumbone lowered the levels of inflammatory biomarkers IL1b, TNF-a and prostaglandin E2 in the mouse colonic mucosa. In a subsequent paper Murakami and co-workers reported suppressive effect of zerumbone on 7,12-dimethylbenz[a]anthracene-and TPA-induced initiation and promotion of skin tumors in ICR mice [66]. Topical application of zerumbone was found to enhance mRNA expression levels of anti-oxidative and phase II xenobiotic metabolizing enzymes manganese superoxide dismutase (MnSOD), glutathione peroxidise-1 (GPx-1), GST-P1 and NQO1 in the mouse epidermis.…”
Section: In Vivo Anti-cancer Effects Of Zerumbonementioning
confidence: 95%
“…Our pervious study revealed that topical application of zerumbone inhibited chemically induced mouse skin papillomagenesis (19). This prompted us to examine whether zerumbone could induce HO-1 expression in mouse skin in vivo.…”
Section: Involvement Of Nrf2-are In Zerumbone-induced Expression Of Hmentioning
confidence: 99%
“…Numerous phytochemicals exert chemopreventive effects through induction of phase 2 detoxifying enzymes and cytoprotective proteins. Zerumbone, a major sesquiterpene found in the rhizomes of Zingiber zerumbet Smith (Zingiberaceae), has been shown to have strong antioxidant (16), antiinflammatory (17), and anticarcinogenic (18,19) properties in several in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%